The Effect of Financial Literacy, Risk Preference and Religiosity on Generation Z’s Investment Interest in the Islamic Capital Market - Ade Eko Setiawan; Raudhoh Musyifah; Heni Noviarita (Journal of Islamic Business and Economic Review, 2021)
In this study was to determine and analyze the effect of financial literacy, risk preference and religiosity on generation z investment interest in the Islamic capital market. The type of research used in this research is qualitative research, with qualitative descriptive research methods. Primary data in this study were obtained by using a questionnaire distributed via google form . The population in this study was generation Z who were students of the Islamic Banking Study Program at Uin Raden Intan Lampung class 2018-2019, totaling 483 people, with a total research sample of 48 respondents. The sampling technique in this research is purvosive sampling. Based on the results of the study, it can be concluded as follows: Financial literacy (X1) partially has no effect on investment interest (Y). Risk preference (X2) partially affects investment interest (Y). Religiosity (X3) partially has no effect on investment interest (Y). Financial literacy (X1), risk preference (X2), and religiosity (X3) simultaneously have no effect on investment interest (Y).